Robin's Inequality for Sum of Divisors Function and the Riemann Hypothesis (Journal of Informatics and Mathematical Sciences, 2012)
Let $σ ( n) $ denote the sum of divisors function. In this paper we give a simple proof of the Robin inequality (R): $σ ( n) (R) implies Riemann Hypothesis.
Keywords: Sum of divisor function; Robin's criterion; Riemann hypothesis